SIN AND TABOO IN ARCHAIC CULTURES - D. V. Pikalov; O. N. Pikalova (Гуманитарные и юридические исследования)
The article studies the reasons of dreadful confrontation between belief systems of domiciled and nomadic population. One of the elements of this ideological opposition is taboo on agriculture, which is typical of some archaic cultures in Ancient Near East and Mesoamerica. The reasons for its origin, peculiarities and social functions are discussed.